(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
This article examines the international legal mechanisms for protecting migrants’ rights in the digital era, emphasizing the role of digital platforms and artificial intelligence (AI) technologies. It analyzes core international treaties and instruments adopted under the auspices of the United Nations (UN), the International Labour Organization (ILO), and other global bodies, along with comparative experiences from the United States, Germany, South Korea, Kazakhstan, and Uzbekistan. The paper highlights both opportunities and risks of implementing digital solutions, such as enhanced accessibility, data protection, cybersecurity, algorithmic transparency, and cross-border cooperation. Based on comparative analysis, it proposes recommendations for improving legal regulation and developing a robust national digital infrastructure for migrant support.